Investigating the antioxidant properties of seaweed treated cotton fabrics for hygienic applications. Issue 6 (19th September 2019) - Janarthanan, M.; Kumar, M. Senthil
Abstract : Purpose: The purpose of this paper is to investigate the efficient exploitation of bioactive compounds present in red, green and brown seaweeds to develop hygienic products. Design/methodology/approach: To analyse the antioxidant properties and identification of significant bioactive compounds of green, red and brown seaweed treated cotton fabrics, total antioxidant activity, DPPH Free radical scavenging activity and gas chromatography-mass spectrometry analysis were used. Findings: The experimental result specifies that the maximum antioxidant activity of 126.50  µ g/ml and inhibition percentage of 76 ± 0.15 percent was achieved in the seaweed treated cotton fabrics. All six seaweed treated fabrics proved slightly lesser water vapour and air permeability compared with the untreated fabric. Originality/value: The seaweed treated cotton materials are suitable for making wound dressing, surgical wear, face mask, sportswear, healthcare and hygienic applications.